In the garden of the righteous : the heroes who risked their lives to save Jews during the Holocaust - Hurowitz, Richard (Harper, an imprint of HarperCollinsPublishers, 2023)
"In the Garden of the Righteous chronicles extraordinary acts at a time when the moral choices were stark, the threat immense, and the passive apathy of millions predominated. Deeply researched, it focuses on ten remarkable stories. These heroes provided hiding places, participated in underground networks, refused to betray their neighbors, and secured safe passage to save the persecuted. They repeatedly defied authorities and risked their lives, their livelihoods, and their families. In the Garden of the Righteous is a profound testament to their kindness and courage"--